Językowy kształt komend w „Piechotnym ćwiczeniu” Błażeja Lipowskiego (1660 r .) - Szczaus, Agnieszka (Studia Europaea Gnesnensia, 2016)
The article focuses on description and analysis of the construction of military commands excerpted from “Piechotne ćwiczenie” by Błażej Lipowski.